ANALISIS MANAJEMEN KAS UNTUK MENJAGA LIKUIDITAS USAHA PADA UD DONNY PIA DI KECAMATAN JENGGAWAH - Akbar, Yugo Ferdian; Kantun, Sri; Tiara, Tiara (Economic Education, University of Jember, 2023)
UD Donny Pia is one of the UMKM players in the manufacturing sector that has implemented cash management and is carried out by a special section. So that researchers are interested in analyzing the cash management carried out. This research is a quantitative descriptive study that aims to describe the application of cash management to maintain business liquidity at UD Donny Pia. The results showed that UD Donny Pia always prepares a cash budget before starting production activities. UD Donny Pia's cash budget is prepared for production needs four days a week and does not include financing transaction posts. UD Donny Pia's cash organization was carried out by accelerating cash receipts from sales and slowing cash disbursements by implementing the purchase of raw materials on credit. UD Donny Pia conducts cash monitoring by applying the obligation to use evidence for each cash transaction, performs computerized cash records, and performs separation between the parties who store cash and those who manage cash. The level of business liquidity is known to be 1.29 which is still below the ideal standard. However, if viewed from the point of view of the ability to pay for production needs, then UD Donny Pia can be said to be in a liquid position. This is because the cash owned by UD Donny Pia is always sufficient to meet production needs. Thus, the implementation of management carried out by UD Donny Pia affects the good liquidity of its business.